Spolna zloraba fantov v otroštvu - Repič, Tanja (Psihološka obzorja (Ljubljana), 2006)
According to the traditional belief, which is still often held to be true, girls and women are thought to be the victims in the majority of sexual abuses, whereas men are the offenders. However several recent researches have shown that also many men find themselves among the victims (3-34%), also from the part of women as offenders. The paper throws light upon, evaluates critically and reviews existing studies on boys as victims of this traumatic experience. It examines closely and describes characteristics of victims (boys) and offenders. Victims of a female offender and a male offender are compared. Further, the family circumstances in which sexually abused boys mostly grow up are analysed.
Keywords: spolna zloraba; social psychology; socialna psihologija; fantje; storilci; družinski odnosi; pedofilija